Laparoscopic detorsion of gangrenous adnexae followed by interval cystectomy: case report and review of the literature - Ramli, Roziana; Mansor, Halimatun; Abdullah, Yusmadi; Mulalek, Noraini; Yusoff, Wan Abu Bakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 15 year old girl presented with a 1-day history of acute abdomen. Abdominal ultrasound revealed a left adnexal cyst measuring 8x7 cm. Laparoscopic examination demonstrated an 8 cm left gangrenous adnexal torsion. After detorsion of the left adnexae, the left fallopian tube appeared to be viable however the left ovary remained the same. Postoperative period was uneventful and serial ultrasound showed persistence of the cyst. The left ovary appeared to be completely viable through a repeat laparoscopic examination 6 weeks later and interval left cystectomy was performed. A twisted gangrenous adnexae could be managed by adnexal sparing surgery successfully.